Anti-biofilm investigation of graphene/chitosan nanocomposites against biofilm producing P. aeruginosa and K. pneumoniae. (15th February 2020) - Muthuchamy, Maruthupandy; Govindan, Rajivgandhi; Shine, Kadaikunnan; Thangasamy, Veeramani; Alharbi, Naiyf S.; Thillaichidambaram, Muneeswaran; Khaled, Jamal M.; Wen, Jun-Li; Alanzi, Khalid F.
Highlights: Anti-biofilm activity of GR/CS NCs showed against P. aeruginosa and K. pneumoniae . Biofilm metabolic assay confirmed by CRA method due to the reduction of EPS. Cell viability and damages of both bacteria using GR/CS NCs by CLSM and SEM. In-vivo toxicity of GR/CS NCs showed 90 % against A. franciscana at 70 μg/mL. Abstract: In this study graphene/chitosan nanoparticles (GR/CS NCs) were developed. The homogenous combination of GR and CS was confirmed by FTIR spectroscopy. The combination of CS with GR sheets reduced the XRD intensity of the GR peak in GR/CS NCs, while TEM images revealed the immobile CS coating of GR sheets. Further, the anti-biofilm activity of GR/CS NCs was tested. The tests showed that the formation of biofilm by Pseudomonas aeruginosa and Klebsiella pneumoniae was inhibited at 40□g/mL GR/CS NCs up to 94 and 92 %, respectively. The intracellular and cell surface damage of the bacteria was observed by CLSM and SEM. Also, GR/CS NCs produced a toxic effect of 90 % on Artemia franciscana at 70□g/mL upon 24 h incubation. The recorded properties of the synthesized GR/CS NCs qualify them as potential agents against multi-drug resistant bacteria.